1991
DOI: 10.1063/1.105587
|View full text |Cite
|
Sign up to set email alerts
|

Controlled growth of 3C-SiC and 6H-SiC films on low-tilt-angle vicinal (0001) 6H-SiC wafers

Abstract: We have found that, with proper pregrowth surface treatment, 6H-SiC single-crystal films can be grown by chemical vapor deposition (CVD) at 1450 °C on vicinal (0001) 6H-SiC with tilt angles as small as 0.1°. Previously, tilt angles of greater than 1.5° were required to achieve 6H on 6H at this growth temperature. In addition, 3C-SiC could be induced to grow within selected regions on the 6H substrate. The 3C regions contained few (or zero) double-positioning boundaries and a low density of stacking faults. A n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(34 citation statements)
references
References 7 publications
0
34
0
Order By: Relevance
“…To realize useful devices, high-quality AlN films on {111} diamond and sharp AlN/diamond {111} interfaces are essential. For GaN/SiC heterostructures, previous studies have revealed that surface steps promote extended crystal defects in heteroepitaxial films grown on SiC [163][164][165]. Bassim et al reported that very low dislocation densities were achieved in GaN films on step-free SiC mesa surfaces [166], and ultraviolet luminescence of GaN pn-junction diodes fabricated on the step-free SiC {0001} surfaces was improved relative to that on atomically flat SiC surfaces with atomic steps [167].…”
Section: Atomically Step-free Surfacesmentioning
confidence: 96%
“…To realize useful devices, high-quality AlN films on {111} diamond and sharp AlN/diamond {111} interfaces are essential. For GaN/SiC heterostructures, previous studies have revealed that surface steps promote extended crystal defects in heteroepitaxial films grown on SiC [163][164][165]. Bassim et al reported that very low dislocation densities were achieved in GaN films on step-free SiC mesa surfaces [166], and ultraviolet luminescence of GaN pn-junction diodes fabricated on the step-free SiC {0001} surfaces was improved relative to that on atomically flat SiC surfaces with atomic steps [167].…”
Section: Atomically Step-free Surfacesmentioning
confidence: 96%
“…25 In our previous study, we investigated the effect of different conditions during the temperature ramp-up prior to epitaxial growth on the carrot defect formation during epitaxial growth on 8 off axis substrates. 26 Also a HCl in situ etching prior to epitaxial growth at a temperature 50 C higher than the growth temperature for the growth of about 20 lm thick 4H-SiC epitaxial layers grown on 4 off axis substrates has been used.…”
mentioning
confidence: 99%
“…The role of surface defects in nucleation of 3C-SiC becomes important on SiC{0001} substrates with small off-angles [32]. Note that spiral growth around threading screw dislocations (TSDs) is not considered in the present model.…”
Section: Theoretical Model Of Sic Homoepitaxymentioning
confidence: 99%
“…The disturbance or instability of step-flow growth can result in nucleation of 3C-SiC and/or stacking fault generation. In an early study by Powell et al [32], homoepitaxy of 6H-SiC on 0.2 ∘ off-axis 6H-SiC(0001) was demonstrated by removal of defective sites by appropriate in situ HCl∕H 2 etching. This process was refined, and relatively large area homoepitaxy of 6H-SiC on nearly on-axis (0001) substrates was achieved under Si-rich conditions [189].…”
Section: Sic Homoepitaxy On Nearly On-axis {0001}mentioning
confidence: 99%